(untitled) (Bulletin KNOB, 1996)
When William III of the house of Orange ascended the English throne in 1689, this led to a great increase in the number of prints of Dutch noblemen’s gardens in the Dutch Republic. After the death of William III such series, each of them depicting one single nobleman’s garden, were only rarely made anymore. Instead of them, bulky volumes of prints of regional sights appeared around 1720, among which bourgeois country estates occupied an important place. The supply of garden prints did not only attract the attention of collectors, but also of foreign architects travelling through The Netherlands, looking for inspiration. For example, around 1700 the German architects Pitzler and Sturm used particular prints for the preparation of their journeys, during the journeys themselves and while working them out. Pitzler, for instance, copied the prints of gardens, instead of drawing them as he had observed them himself. Consequently, the observations of travellers were already partly influenced during the journey, channelled or even replaced by prints. For a research of the reception of elements of Dutch garden art in Germany one should therefore focus, more than has been done so far, on the question when the representations of particular gardens and garden elements were published and distributed in copper engravings. It is only on the strength of such a research that one can indicate examples on a wider basis, mark periods of influence and thus put an end to the speculative character of the proposition that a significant Dutch influence on German garden design did indeed exist.